Liver stiffness measurement to platelet ratio index predicts the stage of liver fibrosis in non‐alcoholic fatty liver disease. Issue 8 (22nd September 2016) - Okajima, Akira; Sumida, Yoshio; Taketani, Hiroyoshi; Hara, Tasuku; Seko, Yuya; Ishiba, Hiroshi; Nishimura, Takeshi; Umemura, Atsushi; Nishikawa, Taichiro; Yamaguchi, Kanji; Moriguchi, Michihisa; Mitsuyoshi, Hironori; et al.
Abstract : Aim: Platelet count and liver stiffness measurement (LSM) using transient elastography could identify significant fibrosis in patients with non‐alcoholic fatty liver disease (NAFLD). We constructed a novel index combining LSM with platelet count for staging fibrosis in Japanese patients with NAFLD. Methods: We recruited 173 Japanese patients with liver biopsy‐proven NAFLD. The areas under the receiver operating characteristic curves were calculated and compared with established parameters and scoring systems for staging liver fibrosis. Results: After excluding 10 patients in whom LSM failed, 163 patients with NAFLD were enrolled. The areas under the receiver operating characteristic curves of the LSM/platelet ratio (LPR) index for detecting fibrosis ≥stage 1, ≥stage 2, and ≥stage 3 were the greatest (0.835, 0.913, and 0.936, respectively) compared with those for various other parameters and established scoring systems, such as LSM, type IV collagen 7 s domain, platelet count, NAFIC score, fibrosis‐4 index, NAFLD fibrosis score, aspartate aminotransferase/alanine aminotransferase ratio, and aspartate aminotransferase to platelet ratio index. The optimal cut‐off, positive predictive, and negative predictive values of the LPR index for detecting ≥stage 3 fibrosis were 0.60, 48.9%, and 99.2%, whereas those of LSM were 10.0 kPa, 35.0%, and 99.0%, respectively. The novel LPR index helps avoid biopsies in a larger percentage of patients with NAFLD compared with that LSM alone. Conclusions: The LPR index was the best predictor for staging fibrosis in patients with NAFLD. It represents a simple and non‐invasive alternative to liver biopsy in clinical practice.